Antarctica: Music, sounds and cultural connections - Hince, Bernadette (ANU Press, 2015)
This is the first book whose subject is the music, sounds and silences of Antarctica. From 2011 until 2014, Australia marked its long-standing connection with Antarctica by celebrating the centenary of the Australasian Antarctic Expedition. The icy continent, with its extremes of climate and environment and unique soundscapes, offers great potential for creative achievements in the world of music and sound. This book demonstrates the intellectual and creative engagement of artists, musicians, scientists and writers. Consciousness of sounds - in particular, musical ones - has not been at the forefront of our aims in polar endeavours, but listening to and appreciating them has been as important there as elsewhere.